Transient Headache and Neurological Deficits with Cerebrospinal Fluid Lymphocytosis Associated with IgM Antibodies to the Epstein-Barr Virus Viral Capsid Antigen - Kossivi Apetse; Ludovic Breynaert; Chloe Butaud; Albert Beschet; Karine Blanc-Lasserre; Loic Ribouillard; Victor Chan (Case Reports in Neurological Medicine)
Some authors have suggested that the syndrome of transient headache and neurological deficits with cerebrospinal fluid lymphocytosis (HaNDL) results from an immunological response directed against a viral agent. Here we report a case of HaNDL in an immunocompetent 19-year-old male that could support this hypothesis.